Analisis Kesulitan Siswa Dalam Mata Pelajaran Matematika di MIN 3 Kota Mataram - Faizun, M; Ramdhani, Suci; Fahrurrozi (SEMESTA: Jurnal Ilmu Pendidikan dan Pengajaran, 2023)
This study aims to determine "Learning Difficulties in Mathematics at MIN 3 Mataram City for the 2020 Academic Year. This is motivated by the results of observations and interviews with researchers where there are still many students who think that mathematics is difficult, and full of numbers and calculations that make students bored Study. The difficulties experienced by students in the learning process in class are the lack of students' ability to count. Students also do not understand and understand the material presented so that during the learning process students who do not understand tend not to pay attention to what the teacher explains. The data collected in this study is in the form of descriptive data obtained through observation, interviews and documentation in the field. Descriptive data, namely data in the form of information or information and not in the form of numbers. So in this study researchers used a qualitative approach. The data analysis technique used is inductive in nature, starting from data collection, data reduction, data presentation to drawing conclusions and the validity of the data is carried out using the triangulation method and reference adequacy. The results of this study indicate that students experience difficulties in understanding the language of the questions, difficulties in operating mathematics, and difficulties in performing calculations. Factors that cause student learning difficulties come from internal factors and external factors. Teachers strive to overcome student learning difficulties by conducting remedial learning, providing motivation and study guidance.